PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATA PELAJARAN IPAS - Cindy Yunita Pratiwi; Sri Handayani; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the effect of the RADEC learning model on creative thinking skills in IPAS subjects for fifth-grade students at SD N Tugu Jebres Surakarta in the 2024/2025 academic year. This research was conducted at SD Negeri Tugu Jebres Surakarta. The subjects of the study were all 27 fifth-grade students. The student population consists of 9 male students and 18 female students. This research is a pre-experimental study with a One Group Pretest-Posttest design. Data collection techniques were carried out through interviews, observation, documentation, and creative thinking ability tests. Data were analyzed using normality tests, homogeneity tests, and t-tests (Paired Sample T-Test) with the help of SPSS 25. The results of the analysis showed that there was a significant effect between the use of the RADEC learning model and students' creative thinking skills.Based on the results of the Paired Sample T-Test, a significance value of 0.000 < 0.05 was obtained, indicating a significant effect. Thus, the RADEC learning model is effective for improving students' creative thinking skills in IPAS subjects for fifth-grade elementary school